2000
DOI: 10.4049/jimmunol.165.9.5227
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-6 and IL-10 Signaling and Stat Activation by Inflammatory and Stress Pathways

Abstract: The development and resolution of an inflammatory process are regulated by a complex interplay among cytokines that have pro- and anti-inflammatory effects. Effective and sustained action of a proinflammatory cytokine depends on synergy with other inflammatory cytokines and antagonism of opposing cytokines that are often highly expressed at inflammatory sites. We analyzed the effects of the inflammatory and stress agents, IL-1, TNF-α, LPS, sorbitol, and H2O2, on signaling by IL-6 and IL-10, pleiotropic cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
111
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 85 publications
4
111
1
1
Order By: Relevance
“…4C). This result is inconsistent with a previous report, which found that inhibition of STAT3 activation contributes to inhibition of IL-6-induced SOCS3 gene expression (19). Our result suggests that IL-6-induced SOCS3 gene expression is not mediated by STAT3 phosphorylation, and this is supported by a recent report which shows that IL-6-induced SOCS3 expression is mediated by p38 MAPK activation (20).…”
Section: Pge 2 Augments Il-10 Biological Activitycontrasting
confidence: 99%
See 1 more Smart Citation
“…4C). This result is inconsistent with a previous report, which found that inhibition of STAT3 activation contributes to inhibition of IL-6-induced SOCS3 gene expression (19). Our result suggests that IL-6-induced SOCS3 gene expression is not mediated by STAT3 phosphorylation, and this is supported by a recent report which shows that IL-6-induced SOCS3 expression is mediated by p38 MAPK activation (20).…”
Section: Pge 2 Augments Il-10 Biological Activitycontrasting
confidence: 99%
“…Because it has been reported that IL-6 also up-regulates SOCS3 gene expression (19), we examined the effect of PGE 2 on IL-6-induced SOCS3 expression. IL-6 increased SOCS3 gene expression by 7.7-fold in THP-1 cells.…”
Section: Pge 2 Augments Il-10 Biological Activitymentioning
confidence: 99%
“…Stress-induced p38 MAPK has been highlighted as a key player in previous studies investigating the cross-talk regulation of IL-6 signaling (8,10,18,37). Furthermore, p38 plays a crucial role in the induction and maintenance of chronic inflammation and is strongly activated in inflammatory arthritis (38).…”
Section: Discussionmentioning
confidence: 99%
“…vious studies on macrophages (8). We therefore used SB202190 to determine whether the inhibitory activity of IL-1␤ was p38 dependent.…”
Section: Honke Et Almentioning
confidence: 99%
See 1 more Smart Citation